Analisis SWOT Strategi Penerimaan Mahasiswa Baru: Tinjauan Pustaka dan Eksplorasi Praktis - Syafril Syafril; Sofia, Sofia; Saputra, Boby; Panyiwi Kessi, Andi Makkulawu (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to determine the implementation of new student admission strategies at STIMI Banjarmasin. This is a descriptive qualitative study aimed at comprehensively describing the phenomena occurring in the field based on non-numerical data collection. The method used is a literature study, which analyzes various theoretical references relevant to the identified problems. Practical exploration refers to a learning or problem-solving approach that emphasizes the direct application of knowledge, skills, and theory in real-world situations or through direct experience, rather than solely through theoretical or abstract study. The analytical tool used is a SWOT analysis, which systematically identifies various factors to formulate a company strategy. This analysis is based on logic that maximizes strengths and opportunities while simultaneously minimizing weaknesses and threats. The results of the study indicate several IFAS and EFAS strategies that STIMI Banjarmasin can implement to increase new student admissions.